(untitled) (Research, Society and Development, 2021)
Objective: To describe the main characteristics of temporal distribution, by age group and sex, of hospital admissions for diseases of the respiratory system in the state of Sergipe, based on the records of hospitalizations in the SUS, in the period from 2015 to 2019. Methodology: This is an ecological study, with a quantitative approach, based on secondary data from DATASUS, through the analysis of AIHs. Results: 33,768 hospitalizations were identified, with the male sex being more prevalent with 53.6%, while there were 46.4% female hospitalizations. The predominant age group was 1 to 4 years with 8,056 hospitalizations. Still, 8.9% hospitalizations were elective and 91.1% were urgent. The highest number of deaths was in 2019 with 886 deaths and the highest mortality rate in 2016 with 12.87%. The average stay was higher in 2019, registering 7.6 days of hospitalization. Discussion: It was found that Sergipe follows national and international data regarding hospitalization for respiratory diseases. In Europe, they cause 660,000 deaths and about 6 million hospitalizations, contributing 7% of all causes of hospitalization, being the third leading cause of death. Final considerations: The study made it possible to know the profile of hospital admissions related to respiratory diseases in Sergipe, serving as a planning tool for strategies aimed at preventing new cases and qualifying assistance.